Anxiety in drug-related criminal prisoners in the mechanics of life - asep, budiasep (Universitas PGRI Semarang, 2025)
Anxiety is a feeling that arises when someone experiences feelings of worry or fear in certain situations. Anxiety not only attacks ordinary people or society but can also attack prisoners. The aim of this research is to determine the factors that cause Anxiety in drug criminal inmates in class IIB prisons in Tegal City. The respondent in this study was 1 prisoner who experienced anxiety, and the informants in this study were 1 friend of the respondent and 1 prison employee. Data collection techniques use direct interviews (face to face), documentation and observation. The research results state that there are three factors that cause prisoners to experience anxiety, namely the prison term, future factors and prison environmental factors. The suggestions of this research are for class IIB prisons in Tegal City to pay more attention to the mental health conditions of prisoners in order to prevent prisoners experiencing anxiety, by providing guidance such as developing personal potential, religious guidance and other activities that can grow self-potential in prisoners. It is hoped that future researchers can develop it further with more variables to achieve better research results.